A programme of research to set priorities and reduce uncertainties for the prevention and treatment of skin disease - Thomas, Kim S.; Batchelor, Jonathan M.; Bath-Hextall, Fiona; Chalmers, Joanne; Clarke, Tessa; Crowe, Sally; Delamere, Finola M.; Eleftheriadou, Viktoria; Evans, Nicholas; Firkins, Lester; Greenlaw, Nicola; Lansbury, Louise E.; et al. (NIHR Health Technology Assessment Programme, 2016)
Background